The Cis-Regulatory Code for Kelch-like 21/30 Specific Expression in Ciona robusta Sensory Organs - Coppola, Ugo; Kamal, Ashwani Kumar; Stolfi, Alberto; Ristoratore, Filomena (Frontiers in Cell and Developmental Biology, 2020)
The tunicate Ciona robusta is an emerging model system to study the evolution of the nervous system. Due to their small embryos and compact genomes, tunicates, like Ciona robusta, have great potential to comprehend uncover genetic circuitry underlying cell specific gene repertoire, among different neuronal cells. Their simple larvae possess a sensory vesicle comprising two pigmented sensory organs, the ocellus and the otolith. We focused here on Klhl21/30, a gene belonging to Kelch family, that, in Ciona robusta, starts to be expressed in pigmented cell precursors, becoming specifically maintained in the otolith precursor during embryogenesis. Evolutionary analyses demonstrated the conservation of Klhl21/30 in all the chordates. Cis-regulatory analyses and CRISPR/Cas9 mutagenesis of potential upstream factors, revealed that Klhl21/30 expression is controlled by the combined action of three transcription factors, Mitf, Dmrt, and Msx, which are downstream of FGF signalling. The central role of Mitf is consistent with its function as a fundamental regulator of vertebrate pigment cell development. Moreover, our results unravelled a new function for Dmrt and Msx as transcriptional co-activators in the context of the Ciona otolith.